Model Permainan Edukasi Peduli Sosial bagi Siswa Sekolah Dasar - Nugraheni Warih Utami; Arbin Janu Setiyowati (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2016)
This study aimed to produce a guideline for the social care educational game for the elementary school students which meet the criteria of accuracy, usefulness, simplicity and attractiveness. This was a research and development study adapted from Borg & Gall model by the data analysis technique using Wilcoxon. This study employed purposive sampling technique. The result of this study found that the guideline of social care educational game met the criteria of accuracy, usefulness, simplicity, and attractiveness for Elementary school students.